2002
DOI: 10.1590/s0034-72992002000200011
|View full text |Cite
|
Sign up to set email alerts
|

Complicações orbitárias em pacientes com sinusite aguda

Abstract: Introdução: As complicações orbitárias das sinusites permanecem como tópico importante dentro da otorrinoloringologia, a despeito do decréscimo de sua prevalência observado após o advento da antibioticoterapia. Objetivo: Tendo por objetivo determinar as características clínicas e terapêuticas nos casos de sinusites complicadas. Forma de estudo: Clínico prospectivo randomizado. Material e método: Realizamos um estudo retrospectivo de 128 pacientes internados nos últimos 15 anos na Divisão de Clínica Otorrinolar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…3,4 Voegels et al 5 reported that the prevalence of nasosinusal infection is high, and that it requires complex and prolonged therapy, particularly in the first and second decades of life. The pathophysiology of rhinosinusitis consists of obstruction of paranasal sinus ostia (which aerate and drain the sinuses).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…3,4 Voegels et al 5 reported that the prevalence of nasosinusal infection is high, and that it requires complex and prolonged therapy, particularly in the first and second decades of life. The pathophysiology of rhinosinusitis consists of obstruction of paranasal sinus ostia (which aerate and drain the sinuses).…”
Section: Introductionmentioning
confidence: 99%
“…There is rhinorrhea, significant nasal block, dry coughing that worsens at night, throat clearing, cacosmia, halitosis, hyposmia, and nasal bleeding in the chronic phase. [1][2][3][4][5][6][7][8] Predisposing factors -such as duration and frequency of crises -are relevant for defining appropriate therapy in chronic rhinosinusitis. [1][2][3][4][5][6][7][8] Recent studies have recommended using systemic or topical drugs and adjuvant therapy.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations